A lahore birth cohort study (LBCS): analysis of the growth and development of Pakistani infants in relation to the nutritional status of their mother and associated risk factors after birth - Amjad, Safeena (2024)
In Pakistan, the prevalence of child malnutrition is higher than in other developing countries. Lahore Birth Cohort Study (LBCS) was conducted to analyze the association between the health and growth of Pakistani infants with maternal nutritional status, depression, and dietary patterns after delivery. The LBCS was a two-year prospective cohort study started in 2020 that recruits Pakistani Infants after their birth from the Punjab Medical Centre Lahore Pakistan. Participants of the study were interviewed three times at birth, at 2.5 months, and at the age of 9 months. The mother’s postpartum information was collected from the hospital records and via a pre-structured questionnaire. Collected data included sociodemographic features, anthropometrics of newborns and mothers, dietary intake of mothers during pregnancy, infant feeding practices after birth, and 2.5 months along with breastfeeding and weaning practices at the age of 9 months. Findings indicate that the continuation of maternal breast milk during the first six months of life protects infants from various forms of malnutrition. It was also found that maternal factors such as postpartum depression (P<0.017) and mother’s occupation (P<0.04) have a significant association with the infant’s growth and development. It was also determined that breastfeeding (P<0.018), bread and cereals (P<0.00), dairy and dairy products (P<0.015), other milk (P<0.00), and meat and meat substitutes (P<0.00) also has a potentially significant association between the variables at 9 months. The correlation coefficient revealed that there is a positive association between postpartum depression and postpartum BMI on infant birth weight for the age Z score, birth weight (percentile), birth height for the age z score, and birth head circumference (percentile). There was a significant correlation between breastfeeding and infant anthropometric measurements at 2.5 and 9 months of age, including length, weight for age, and head circumference percentile. The strength of these associations increased by 9 months, indicating that breastfeeding's effect on growth parameters persists and even intensifies as infant grows. In conclusion, the Lahore Birth Cohort Study contributes crucial insights into the multifaceted relationship between breastfeeding, maternal factors, and infant growth. The findings emphasize the persistent and intensifying impact of breastfeeding, guiding healthcare recommendations and underlining the need for holistic support for infant health in the Pakistani context.